Audit Experience, Role Clarity, and Lifestyle as Drivers of Auditor Performance: Pengalaman Audit, Kejelasan Peran, dan Gaya Hidup sebagai Pendorong Kinerja Auditor - Andari, Miranda Putrin; Hermawan, Sigit (Indonesian Journal of Law and Economics Review, 2024)
Background: Auditor performance is essential for reliable financial reporting, influenced by factors like experience, role ambiguity, and lifestyle. Gap: The role of spiritual intelligence as a mediator in these relationships is not well explored. Aim: This study examines the impact of audit experience, role ambiguity, and lifestyle on auditor performance, with spiritual intelligence as an intervening variable. Results: Analyzing data from 65 auditors using Partial Least Square (PLS), findings reveal that experience, ambiguity, and lifestyle significantly affect auditor performance and spiritual intelligence (p < 0.05), with spiritual intelligence also mediating these relationships. Novelty and Implications: Introducing spiritual intelligence as a mediating factor offers new insights, suggesting its value in enhancing auditor well-being and performance. Highlights : Audit experience, role ambiguity, and lifestyle significantly influence auditor performance. Spiritual intelligence acts as a mediating factor between personal factors and performance. Enhancing spiritual intelligence can improve auditor resilience and productivity. Keywords: Auditor, Performance, Spiritual Intelligence, Role Ambiguity, Lifestyle